Relationship Between Parents And Events Low Birth Weight - Asnidar; Asdinar (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Babies are said to be Low Birth Weight (LBW) if the baby's birth weight is <2500 grams. Several factors influence LBW incidence, one of which is maternal parity. The purpose of this study is to know the relationship between maternal parity and LBW events in the Scope of Work in Lembanna Public Health Center, Kajang Sub-district, Bulukumba Regency in 2016-2017. This research uses an analytic observational design with a historical cohort approach. while the sample in this study amounted to 42 LBW infants using total sampling techniques and 42 non LBW infants using random sampling techniques. Based on the results of statistical analysis of the relationship with LBW events in the Scope of Work in the Health Center of Lembanna, Kajang District, Bulukumba Regency, 2016-2017 using the test chi-square, with a level of confidence (Î± = 0.05). Based on the test results obtained value (p = 1,000) then Ho is accepted and Ha is rejected. So it can be concluded that,